Potencial terapêutico do extrato metanólico de Condalia buxifolia reissek no controle da dor aguda: estudo do mecanismo de ação - Simões, Róli Rodrigues (2015)
The medicinal plant Condalia buxifolia has been traditionally used to treat inflammatory processes. The present study aimed to evaluate the phytochemical profile and the analgesic effect of the methanolic extract from the root bark of Condalia buxifolia (MECb) in models of acute pain as well as to investigate the possible adjacente mechanism of its effect in mice. The phytochemical analysis of the extract showed the presence of large amounts of alkaloids. The MECb administered intragastrically 1 hour before the experiments (100 and 300 mg/kg, ig), mimicking the route used in humans (oral), promoted reduction of the nociceptive inflammatory pain (2nd phase) and paw oedema induced by intraplantar (i.pl.) injection of formalin, and its antiedematogenic and analgesic effect lasted until 4 and 6 h after MECb pretreatment. MECb (10-300) also prevented nociception induced by intraperitoneal injection of acetic acid. Furthermore, MECb (100 mg/kg, i.g.) prevented paw oedema and nociception induced by i.pl. injection of capsaicin, acidified saline, and nociception glutamate-induced by i.pl. injection. Centrally, MECb increased the latency to nociceptive stimulation in the hot plate model. Moreover, the opioid system is involved in the mechanism of action of MECb, since its effect (at the dose of 300 mg/kg, i.g.) was reversed by naloxone (an antagonist of opioid receptor). Acute (prolonged) treatment with MECb (100 mg/kg, i.g.) reduced the mechanical and thermal (heat) hyperalgesia caused by plantar incision (PI), a model of postoperative pain; and prevented the increase of the concentration of inflammatory cytokines [interleukin-1 β (IL-1 β), tumor necrosis factor-α (TNF-α)] and neurotrophin [nerve growth factor (NGF)]. Additionally, MECb was able to prevent nociception induced by PLC/PKC and cAMP/PKA pathway activators, PMA, forskolin and PGE2. Furthermore, MECb was also able to reduce PKA activation, demonstrated by western blotting analysis, suggesting that the MECb can act by interaction with this signaling pathway. Intrathecal treatment with capsaicin (for desensitization of C fibers) does not alter the mechanical hyperalgesia induced by IP and ablation did not influence the analgesic effect of MECb. Finally, MECb caused no sedative effects or alterations on motor activity of the animals in the open field test and the prolonged treatment did not promote macroscopic changes in important organs (liver, heart, spleen, kidneys and lungs), or changes in hematological and biochemical parameters (glucose, urea, creatinine, uric acid, AST, ALT, GGT, total cholesterol, HDL and LDL), and did not change the profile of food and water intake. Taken together, the results show that the antinociceptive effect of MECb is due, in part, by activation of the opioid system and inhibition of glutamatergic system, pro-inflammatory cytokines and TRPV1 and ASICs channels, as well as the PLC/PKC and/or cAMP/PKA signaling-dependent inhibition. Thus, the results of this study support that Condalia buxifolia has potential effect on pain control, and the continuity of extensive preclinical and clinical studies for the development of an analgesic phytoterapic.